In line 40 Gb/s group‐velocity dispersion monitoring. Issue 1 (25th November 2013) - Sousa, A.; Andre, P.
ABSTRACT In this article, we propose a technique to monitor the group‐velocity dispersion (GVD) of an optical signal modulated at 40 Gb/s. The described method is based on the measurement of the electrical signal power at the clock frequency and is able to return the magnitude value and sign of the GVD. We show that this technique is capable to return the GVD in the range [−60, 60] ps/nm, with an error of 3 ps/nm. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:206–208, 2014